CONTRIBUTION TO EARLY STUDY OF TILLERING IN HARD WHEAT - H. Zeddig; A. Ghennai; C. Zerafa; M. Benlaribi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The study was conducted by D.V.P.R at the University of Brothers Mentouri Constantine 1 (Algeria). This anatomical study was conducted to follow-up the formation of wheat Triticum durum Desf. tillers Using tissue sections the manual way in the seed (during germination) and the shoot ( first leaf stage F 1, the second leaf F2, the third leaf F3) and coloring them with the (carmine-green iodine) and then observed with the optical microscope Leica. The results revealed that the shoot apical meristem SAM and the root apical meristem RAM are two of the key parameters that provide embryonic growth cells. It also does not show this stage formation bud tillering during the germination of the seeds. While it initiated formation during the emergence of the second leaf (F2) Where we observe appearance of a cellular mass that is adopted as primary meristem, the development of tiller bud during the first three stages of the leaf, so that the AXM axillary formation begins in the axils of the leaf and then the formation of the bud and bud growth to form the tiller. Each tiller had ability to produce the spikes. This is considered one of the main factors determining production.